2002
DOI: 10.1124/jpet.301.1.197
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Haloperidol and Clozapine on [3H]cAMP Binding, Protein Kinase A (PKA) Activity, and mRNA and Protein Expression of Selective Regulatory and Catalytic Subunit Isoforms of PKA in Rat Brain

Abstract: The present study was undertaken to examine whether the mechanism of action of typical and atypical antipsychotics is related in their ability to regulate key phosphorylating enzyme of adenylyl cyclase-cAMP pathway, i.e., protein kinase A (PKA). For this purpose, regulatory (R) and catalytic (Cat) activities of PKA and expression of various isoforms of regulatory and catalytic subunits were examined in rat brain after single or chronic (21-day) treatment with haloperidol (HAL, 1 mg/kg) or clozapine (CLOZ, 20 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
69
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 35 publications
8
69
0
Order By: Relevance
“…Amphetamine, an indirect dopaminergic agonist, decreases PPI via dopamine D2 receptors (Ralph-Williams et al, 2002) that inhibit AC activity (Neves et al, 2002). Conversely, haloperidol, a typical antipsychotic that blocks D2 receptors (cf., Miyamoto et al, 2005) and increases cAMP signaling in forebrain structures (Berndt and Schwabe, 1973;Kaneko et al, 1992;Kaplan et al, 1999;Dwivedi et al, 2002; but see Kebabian et al, 1972;Carenzi et al, 1975), increases PPI (Ouagazzal et al, 2001). Thus, there appears to be a relationship between cAMP and PPI levels.…”
Section: Introductionmentioning
confidence: 96%
“…Amphetamine, an indirect dopaminergic agonist, decreases PPI via dopamine D2 receptors (Ralph-Williams et al, 2002) that inhibit AC activity (Neves et al, 2002). Conversely, haloperidol, a typical antipsychotic that blocks D2 receptors (cf., Miyamoto et al, 2005) and increases cAMP signaling in forebrain structures (Berndt and Schwabe, 1973;Kaneko et al, 1992;Kaplan et al, 1999;Dwivedi et al, 2002; but see Kebabian et al, 1972;Carenzi et al, 1975), increases PPI (Ouagazzal et al, 2001). Thus, there appears to be a relationship between cAMP and PPI levels.…”
Section: Introductionmentioning
confidence: 96%
“…Specifically, an involvement of some enzymes, which are known to be changed in schizophrenia and are affected by antipsychotic drugs, that is, PKA, protein kinase C (PKC), protein kinase B (PKB; Akt), glycogen synthase kinase-3 (GSK-3), Ca 2 + /calmodulin-dependent protein kinase (CaMK), and mitogen-activated protein kinase (MAPK), in the inhibitory action of chlorpromazine and clozapine on CRH gene promoter activity was determined (Dwivedi and Pandey, 1999;Dwivedi et al, 2002;Lu et al, 2004;Ninan et al, 2003;Yang et al, 2004). We chose for this study chlorpromazine, a classical antipsychotic drug and a atypical antipsychotic clozapine, because in the first part of study they showed the most potent inhibitory effects on the CRH gene activity.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] This possibility is supported by recent studies showing that adrenal glucocorticoids modulate the levels and the activity of PKA. 20 Alternatively, the observed modifications may be ascribed to altered circulating levels of monoamines and metabolites. 14 Another possibility is that the altered levels of PKA may reflect adaptive responses to other dysfunctions in signal transduction such as Ca 2+ signaling and the phosphoinositides cycle, including protein kinase C. 2,21,22 In this regard, it is interesting to note that components of the phosphoinositide cycle, such as phospholipase C and protein kinase C, could also be regulated by administration of dexamethasone.…”
Section: Figurementioning
confidence: 99%
“…Medical health was documented by the medical history, physical examination, electrocardiography, blood and serum chemical analyses (including hepatic and renal profiles), and thyroid function tests. The severity of symptomatology was evaluated using the global score of the 21-item Hamilton Rating Scale for Depression 28 (HRSD) and the delusion factor (items 2,15,20). [28][29][30] The HRSD was administered by trained psychiatrists, who had a good inter-rater reliability.…”
Section: Subjectsmentioning
confidence: 99%